2013
DOI: 10.1007/s40268-013-0004-x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Efficacy of an Emollient Containing Ceramide-Precursor Lipids and Moisturizing Factors for Atopic Dermatitis in Pediatric Patients

Abstract: BackgroundAtopic eczema or dermatitis (AD) is associated with atopy and is characterized by reduced skin hydration and an impaired skin barrier in the epidermis. We investigated the patient acceptability and efficacy of an emollient containing ceramide-precursor lipids and moisturizing factors (LMF) in AD.MethodsConsecutive AD patients were recruited. Swabs and cultures were obtained from the right antecubital fossa and the worst-affected eczematous area, and disease severity [according to the SCORing Atopic D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 26 publications
2
29
0
2
Order By: Relevance
“…Standardization of TEWL measurements can be technically difficult and similar paradoxical findings have been reported in other moisturizer studies [13, 31, 34, 35]. Furthermore, SC hydration is a more sensitive measure of the skin barrier function than TEWL in AD patients [36], as the relationship between TEWL and skin dryness is complex, whereby changes in dryness do not necessarily reflect simultaneous changes in TEWL [37].…”
Section: Discussionmentioning
confidence: 74%
“…Standardization of TEWL measurements can be technically difficult and similar paradoxical findings have been reported in other moisturizer studies [13, 31, 34, 35]. Furthermore, SC hydration is a more sensitive measure of the skin barrier function than TEWL in AD patients [36], as the relationship between TEWL and skin dryness is complex, whereby changes in dryness do not necessarily reflect simultaneous changes in TEWL [37].…”
Section: Discussionmentioning
confidence: 74%
“…Clinical studies have demonstrated that topical moisturizer alone improves psoriasis . Previous studies have shown that both Cer and glycerol, ingredients in our moisturizer, increase SC hydration in normal and diseased skin . In addition, the activation of PPARγ by LA upregulates aquaporin 3 expression , which in turn increases skin hydration .…”
Section: Discussionmentioning
confidence: 96%
“…Although we found high representation of comparisons with inactive controls, these may not be true placebos because they are not totally inactive despite their lack of active principle (Shamsudin and Fleischer, 2010). Indeed, applying excipients on the skin induces physiochemical modifications of the skin barrier, which were demonstrated with transepidermal water loss (Hon et al, 2013). We found the use of inactive controls particularly frequent in studies on CLEWs.…”
Section: Discussionmentioning
confidence: 79%